A novel method for comparing radiation dose and image quality, between and within different x-ray units in a series of hospitals - Al-Murshedi, Sadeq (2019)
Objectives - To develop a novel method for comparing radiation dose and image quality (IQ) to evaluate adult chest x-ray (CXR) imaging among several hospitals. Methods - CDRAD 2.0 phantom was used to acquire images in eight hospitals (17 digital x-ray units) using local adult CXR protocols. IQ was represented by image quality figure inverse (IQFinv), measured using CDRAD analyser software. Signal to noise ratio, contrast to noise ratio and conspicuity index were calculated as additional measures of IQ. Incident air kerma (IAK) was measured using a solid-state dosimeter for each acquisition. Figure of merit (FOM) was calculated to provide a single estimation of IQ and radiation dose. Results - IQ, radiation dose and FOM varied considerably between hospitals and x-ray units. For IQFinv, the mean (range) between and within the hospitals were 1.42 (0.83-2.18) and 1.87 (1.52-2.18), respectively. For IAK, the mean (range) between and within the hospitals were 93.56 (17.26-239.15) μGy and 180.85 (122.58-239.15) μGy, respectively. For FOM, the mean (range) between and within hospitals were 0.05 (0.01-0.14) and 0.03 (0.02-0.05), respectively. Concluysions - The suggested method for comparing IQ and dose using FOM concept along with the new proposed FOM, is a valid, reliable and effective approach for monitoring and comparing IQ and dose between and within hospitals. It is also can be beneficial for the optimisation of x-ray units in clinical practice. Further optimisation for the hospitals/x-ray units with low FOM are required to minimise radiation dose without degrading IQ.